Elders Rising : The Promise and Peril of Aging - Martinson, Roland D., 1942- (Word & world books., 2019)
Riding the age wave with grace. In this inspiring book, Roland D. Martinson draws on the folk wisdom and experience of over fifty persons between the ages of sixty-two and ninety-seven. He puts this wisdom in conversation with scriptural and theological understandings of elders in the last third of life and sets forth perspectives on aging for individuals, groups, civic organizations, and congregations to utilize in developing a vital, resilient, and productive quality of life for elders. The book explores some current age-wave numbers and explores elderhood in relation to Scripture, theology, and the wisdom of "pioneers and pathfinders." Practical direction is given for conversation and action based on exploring elder identity, presence, partnerships, passions, purpose, powers, and promise. Martinson lays out a process for helping communities, including faith communities, become "vital aging centers" where elders are called to look honestly and hopefully at life's third chapter and to make it a time of discovery, adventure, and capacity. The volume will help congregations better serve the needs of elders and integrate elder wisdom and capacity in their mission and ministry.